Survival and root structure changes of rice seedlings in different cultivars under submergence condition - Diah Rachmawati; M.M. MARYANI; SUHESTI KUSUMADEWI; FITRI RAHAYU (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Rachmawati D, Maryani MM, Kusumadewi S, Rahayu F. 2019. Survival and root structure changes of rice seedlings in different cultivars under submergence condition. Biodiversitas 20: 3011-3017. Submergence affects plant growth and fitness in natural and agricultural ecosystem. Plant survival to submergence is strongly influenced by the water level and duration of submergence. The objective of this study was to determine the survivalysiological and root anatomical changes of two rice cultivars seedlings to submergence The experiment used completely randomized design with three factors, cultivar (IR-64’ and ‘Inpara 5’), depth and duration of submergence. Depth of submergence consisted of 3 levels: without, partial and complete submergence. Fourteen days old seedlings were treated for 5, 10 and 15 days of submergence. The observed parameters were seedling survival, chlorophyll content, soluble sugar and starch content, plant biomass, and root anatomical structure. The results showed that seedlings survival of ‘IR-64’ and ‘Inpara 5’ decreased by increasing depth and duration of submergence. Increasing depth of submergence decreased chlorophyll content, soluble sugar content and plant biomass. Anatomically, depth and duration of submergence showed a greater increased in root cortex thickness, aerenchyma tissue diameter and the percentage of cortex to be aerenchyma of rice ‘IR-64’ and ‘Inpara 5’. Fifteen days of complete submergence significantly decreased seedlings survival and increased the diameter of aerenchyma in both ‘IR-64’ and ‘Inpara 5’.